![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(-3x+2\right)-\left(5-3x\right)=-3\)
\(\Rightarrow-3x+2-5+3x=-3\)
\(\Rightarrow-3x+3x=-3+5-2\)
\(\Rightarrow0x=0\Rightarrow x\in Z\)
\(3+x-\left(3x-1\right)=6-2x\)
\(\Rightarrow3+x-3x+1=6-2x\)
\(\Rightarrow x-3x+2x=6-1-3\)
\(\Rightarrow0x=2\left(loại\right)\)
\(\left(x-5\right)\left(3x+4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\3x+4=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\x=-\frac{4}{3}\end{cases}}}\)
\(7x\left(2x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}7x=0\\2x-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{2}\end{cases}}}\)
\(\left(3x-1\right)2x=0\)
\(\Leftrightarrow\orbr{\begin{cases}3x-1=0\\2x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=0\end{cases}}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3x - 4 (2x-7) = 3x - 3
3x - 8x + 28 = 3x - 3
=> 3x - 8x - 3x = -3 -28
-8x = -31
x = 31/8
b) 3(2x-7) - (4-2x) = 2x -1
6x - 7 - 4 + 2x = 2x -1
=> 6x + 2x - 2x = -1 + 7+4
6x = 10
x = 5/3
c) (x-2).(2x+12)=0
=> x -2 = 0 => x = 2
2x + 12 = 0 => 2x = -12 => x = -6
KL: x = 2 hoặc x = -6
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
<=> 3x - 3 + x - 2 = 2x - 2 - x + 1
<=> 3x + x - 2x + x = -2 + 1 + 3 + 2
<=> 3x = 4
<=> x = 4/3
Các câu sau làm tương tự
\(\left(3x-3\right)+\left(x-2\right)=\left(2x-2\right)-\left(x-1\right)\)
<=> \(3x-3+x-2=2x-2-x+1\)
<=> \(4x-5=x-1\)
<=> \(3x=4\)
<=> \(x=\frac{4}{3}\)
Vậy....
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left|x^2+1\right|=2x^2\)
\(\Rightarrow\orbr{\begin{cases}x^2+1=2x^2\\x^2+1=-2x^2\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x^2=1\\\text{loại}\end{cases}}\)
\(\Rightarrow x\in\left\{\pm1\right\}\)
b) \(\left|3x-1\right|+2x=\left|1-3x\right|+4\)
\(\left|3x-1\right|+2x=\left|3x-1\right|+4\)
\(2x=4\)
\(x=2\)
Vậy.....
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2\left(x-1\right)+3\left(3x-2\right)=x-4\)
\(2x-2+9x-6=x-4\)
\(2x+9x-x-2-6=-4\)
\(10x-2-6=-4\)
\(10x-2=2\)
\(10x=4\)
\(x=\frac{2}{5}\)
Vậy \(x=\frac{2}{5}\)
\(3\left(4-x\right)-2\left(x-1\right)=x+20\)
\(12-3x-2x+2=x+20\)
\(12-5x+2=x+20\)
\(12-5x-x+2=20\)
\(12-6x+2=20\)
\(12-6x=18\)
\(6x=-6\)
\(x=-1\)
Vậy \(x=-1.\)
\(4\left(2x+7\right)-3\left(3x-2\right)=24\)
\(8x+28-9x+6=24\)
\(8x-9x+28+6=24\)
\(-x+34=24\)
\(-x=-10\)
\(x=10\)
Vậy \(x=10\)
\(3\left(x-2\right)+2x=10\)
\(3x-6+2x=10\)
\(3x+2x-6=10\)
\(5x=16\)
\(x=\frac{16}{5}\)
Vậy \(x=\frac{16}{5}\)
2(x-1)+3(3x-2)=x-4
=>2x-2=9x-6-x+4=0
=>10x-4=0
=>x=\(\frac{2}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
5)
để \(\frac{5x-3}{x+1}\)là số nguyên
\(5x-3⋮x+1\)
\(x+1⋮x+1\)
\(\Rightarrow5\left(x+1\right)⋮x+1\)
\(5x-3-\left(5x-5\right)⋮x+1\)
\(-2⋮x+1\)
\(\Rightarrow x+1\inƯ\left(2\right)=\left\{\pm1;\pm2\right\}\)
x+1 | 1 | -1 | 2 | -2 |
x | 0 | -2 | 1 | -3 |
Vậy \(x\in\left\{0;-2;1;-3\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x-1).(2x+1)-(4x+3).(x-2)=3x-1
2x ( 2x-1) - 1(2x+1) - 4x(x-2) + 3( x-2) = 3x-1
4x^2 - 2x - 2x -1 - 4x^2 + 8 + 3x - 6 = 3x- 1
-x + 1= 3x - 1
3x + x = 1+1
4x = 2
x= 1/2
( 2x - 1 ) . ( 2x + 1 ) - ( 4x + 3 ) . ( x - 2 ) = 3x - 1
2x . ( 2x - 1 ) - 1 . ( 2x + 1 ) - 4x . ( x - 2 ) + 3 . ( x - 2 ) = 3x - 1
4x2 - 2x - 2x - 4 - 4x2 + 8 + 3x - 6 = 3x - 1
-x + 1 = 3x - 1
3x + x = 1 + 1
4x = 2
x = 1/2
ta có
-2x+-1=3x+-2
-2x+-1--2 = -3x
-2x+(-1--2) = -3x
-2x+1 = -3x
-3x--2x =1
-1x= 1
x= 1 : (-1)
x= -1
Ta có : \(\left|2x+1\right|\ge0\forall x\)
\(\Rightarrow\left|2x+1\right|=2x+1\)
Mặt khác : \(\left|3x+2\right|\ge0\forall x\)
\(\Rightarrow\left|3x+2\right|=3x+2\)
mà \(\left|2x+1\right|=\left|3x+2\right|\)
\(\Rightarrow2x+1=3x+2\)
\(2x-3x=2-1\)
\(-x=1\)
\(x=-1\)